2017
DOI: 10.1509/jmr.14.0237
|View full text |Cite
|
Sign up to set email alerts
|

Does “Liking” Lead to Loving? The Impact of Joining a Brand's Social Network on Marketing Outcomes

Abstract: Does “liking” a brand on Facebook cause a person to view it more favorably? Or is “liking” simply a symptom of being fond of a brand? The authors disentangle these possibilities and find evidence for the latter: brand attitudes and purchasing are predicted by consumers' preexisting fondness for brands, and these are the same regardless of when and whether consumers “like” brands on social media. In addition, we explore possible second-order effects by examining whether “liking” brands might cause consumers' fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
3
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 24 publications
2
101
3
1
Order By: Relevance
“…However, she comes at a high price: one post that Selena sponsors for a brand can cost upwards of $800,000 (Mejia 2018). However, putting high valuations on mere online exposures or collecting Blikes^for specific posts can be somewhat speculative, as academic research shows that acquiring Blikes^on social media might have no effect on consumers' attitudes or behaviors (John et al 2017;Mochon et al 2017). Moreover, Hennig-Thurau et al (2015), show that while garnering positive WOM has little to no effect on consumer preferences, negative WOM can have a negative effect on consumer preferences.…”
Section: The Rise Of New Forms Of Social Influence (And Influencers)mentioning
confidence: 99%
“…However, she comes at a high price: one post that Selena sponsors for a brand can cost upwards of $800,000 (Mejia 2018). However, putting high valuations on mere online exposures or collecting Blikes^for specific posts can be somewhat speculative, as academic research shows that acquiring Blikes^on social media might have no effect on consumers' attitudes or behaviors (John et al 2017;Mochon et al 2017). Moreover, Hennig-Thurau et al (2015), show that while garnering positive WOM has little to no effect on consumer preferences, negative WOM can have a negative effect on consumer preferences.…”
Section: The Rise Of New Forms Of Social Influence (And Influencers)mentioning
confidence: 99%
“…Calder, Malthouse, and Schaedel () in a study of engagement with website advertising found that interactive engagement was associated with advertising effectiveness which was measured as ‘reactions to the ad’ and ‘likelihood to click through’. However, one of the challenges in measuring engagement arises from the differences between platforms and the ways consumers can engage on various platforms (Barger et al, ; Coursaris, Osch, & Balogh, ; John et al, ). For example, Instagram allows for likes and comments but not shares (as do Facebook and LinkedIn) or retweets (as does Twitter).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, one of the challenges in measuring engagement arises from the differences between platforms and the ways consumers can engage on various platforms (Barger et al, 2016;Coursaris, Osch, & Balogh, 2016;John et al, 2017). For example, Instagram allows for likes and comments but not shares (as do Facebook and LinkedIn) or retweets (as does Twitter).…”
Section: Consumer Engagementmentioning
confidence: 99%
“…The main objective of the present study was to identify the key factors related to the management of environmental issues by Swiss hotels, taking into account the feelings of travelers' reviews during their hotel stay [73][74][75]. The sample was made up of the best 25 hotels in Switzerland according to the ranking of TripAdvisor Traveler's Choice Awards, which was drawn from more than 500 million opinions in Switzerland.…”
Section: Samplementioning
confidence: 99%
“…To identify the indicated indicators, the data extraction resulted in a total sample of n = 8331 reviews extracted from the TripAdvisor API from 19 December 2017 to 15 January 2018, according to the official profiles of Swiss hotels that won the TripAdvisor Traveler's Choice Award [75][76][77].…”
Section: Samplementioning
confidence: 99%